Mechanisms of cellular fibrosis associated with cancer regimen-related toxicities - Mancini, Maria L.; Sonis, Stephen T. (Frontiers in Pharmacology, 2014)
Fibrosis is a common, persistent and potentially debilitating complication of chemotherapy and radiation regimens used for the treatment of cancer. The molecular mechanisms underlying fibrosis have been well studied and reveal overall processes that are largely ubiquitous. However, it is important to note that although the processes are similar, they result in cellular phenotypes that are highly tissue specific. These tissue specific differences may present opportunities for therapeutic interventions to prevent or treat this often irreversible condition. Data generated from animal models of cancer therapy-related tissue toxicities have revealed that the signaling pathways involved in fibrosis are the same as those involved in the normal injury response and include the transforming growth factor β superfamily and a range of pro-inflammatory cytokines. The critical difference between normal wound healing and fibrosis development appears to be, that in fibrosis, these signaling pathways escape normal cellular regulation. As a result, an injury state is maintained and processes involved in normal healing are usurped. There are a few, if any, therapeutics that effectively prevent or treat fibrosis in patients. Consequently, cancer survivors may be chronically plagued with a variety of life-altering fibrosis-related symptoms. Uncovering the signaling pathways that drive cellular fibrosis is paramount to the development of specific therapeutics that will mitigate this potentially devastating condition.